2002
DOI: 10.1002/1522-2675(200209)85:9<2777::aid-hlca2777>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: b ) Departement Chemie, ETH Hˆnggerberg, CH-8093 Z¸rich Chimeric DNA molecules containing four different linking groups, the natural phosphate, 5'-methylenephosphonate, bis(methylene)phosphinate, and bis(methylene) sulfone (see Fig. 1), were directly compared for their ability to form duplexes with complementary DNA and DNA chimeras. From melting temperatures for analogous complementary sequences, general conclusions about the impact of geometric distortion of the internucleotide linkage around the two PÀOÀC b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Thermal stability experiments (T m evaluations) with complementary ODN were conducted along with resistance evaluation against SVPDE. The presence of VP linkages destabilized the duplexes formed with the complementary (d(A 14 )) by À3 1C per modification (comparable to the EtP linkage 203 ). Nuclease digestion experiments showed that the VP linkage, as the EtP one, 202 is totally resistant to SVPDE over 20 min.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stability experiments (T m evaluations) with complementary ODN were conducted along with resistance evaluation against SVPDE. The presence of VP linkages destabilized the duplexes formed with the complementary (d(A 14 )) by À3 1C per modification (comparable to the EtP linkage 203 ). Nuclease digestion experiments showed that the VP linkage, as the EtP one, 202 is totally resistant to SVPDE over 20 min.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
“…The repulsion between the nucleobase and the hydrogen atom(s) at the C6 0 -position induces deleterious effects on the duplex formation as demonstrated on EtP and VP internucleoside linkages. 203,204 The authors synthetized EP linked thymidine dinucleotides having either two natural riboses or one LNA modified nucleoside (Fig. 11).…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
“…Indeed, Benner and co‐workers have studied the physical and chemical effects of sulfone analogues of oligonucleotides extensively 109. 110 In contrast to the approach of Benner, Gervay‐Hague et al. have used a unique disulfone/diphosphonate reagent 16 (Figure 18) to synthesize a large number of highly functionalized geminal disulfone‐containing compounds through Horner–Emmons–Wadsworth (HEW) olefination chemistry 111.…”
Section: Integrasementioning
confidence: 99%
“…Although the crystal structure of dinucleoside analog r(G SO2 C) reveals an only slightly distorted Watson-Crick miniduplex [83], all sulfone-linked octamers do not base pair with complementary oligonucleotides but self-associate and form very stable self-folded structures instead [80,84]. The authors conclude that the absence of the negative charge greatly facilitates formation of the self-structures and that any genetic molecule using Watson-Crick base pairing template must have a charged backbone [85,86].…”
Section: Dimethylene Sulfonesmentioning
confidence: 99%